Curtailing the conventional dose of Folltropin-V for superstimulation and embryo recovery in Sahiwal cattle (Bos indicus) - SINGHAL, SUMIT; SINGH, NARINDER; SINGH, HARPREET; MALIK, V S; BRAR, P S (The Indian Journal of Animal Sciences, 2021)
High cost of the follicle stimulating hormone (FSH) impacted embryo transfer technology (ETT) work in India. The experiment evaluated effects of reduced (200 mg vs 400 mg) FSH (Folltropin-V) dose on superovulation and embryo recovery in Sahiwal cattle. Animals treated with conventional dose of Folltropin, i.e. 400 mg (G1, n=6) were compared with another group administered with half dose (i.e. 200 mg) of Folltropin (G2, n=6). Superstimulatory response (number of follicles >8 mm) during estrus; unovulatory follicles, superovulatory response (one day prior to embryo flushing) using trans-rectal ultrasonography were recorded. Embryos were collected nonsurgically on day-7 post insemination and total recovered and transferable embryos were noted. Results revealed that number of follicles during estrus and subsequent ovulations were significantly higher in the G1 compared to G2 (30.0±1.37 and 26.3±0.99 vs. 20.3±0.21 and 17.7±0.42, respectively). Unovulatory follicles per animal were lower (2.6±0.21 vs. 3.7±0.49) in G2 than G1. The group receiving lower dose of Folltropin (G2) had significantly higher average embryo recovery compared to G1 (12.0±0.63 vs 8.7±0.76, respectively). Additionally, average number of transferable embryos were non-significantly higher in G2 (7.0±0.37) than G1 (5.7±0.88). The study indicated that lower dose of Folltropin-V (200 mg compared to 400 mg) is more effective in superovulation and embryo production in Sahiwal cows.